Macrophages and the microbiome in chronic obstructive pulmonary disease - Karanjot K. Sandhu; Aaron Scott; Amanda L. Tatler; Kylie B.R. Belchamber; Michael J. Cox (European Respiratory Review)
COPD is a heterogeneous disease of the lungs characterised by restricted airflow. Chronic inflammation and recurrent bacterial infections are known to be important driving factors in exacerbations of this disease. Despite a marked increase in the number of alveolar macrophages present in the lungs of COPD patients, there is evidence of reduced clearance of pathogenic bacteria, leading to recurrent infection, exacerbation and subsequent lung function decline. This is thought to be attributed to a defect in the phagocytic capability of both alveolar and monocyte-derived macrophages in COPD. In addition to this defect, there is apparent selectivity in bacterial uptake by COPD macrophages because certain pathogenic genera, such as Haemophilus, Moraxella and Streptococcus, are taken up more readily than others. The respiratory microbiome plays a key role in regulating the host immune response both in health and during chronic inflammation. In patients with COPD, there are distinct changes in the composition of the respiratory microbiome, particularly the lower respiratory tract, where dominance of clinically relevant pathogenic species is commonly observed. Whether there are links between these changes in the microbiome and dysfunctional macrophage phagocytosis has not yet been widely studied. This review aims to discuss what is currently known about these phenomena and to explore interactions between macrophages and the respiratory microbiome.